Detection of novel respiratory viruses from influenza‐like illness in the Philippines - Furuse, Yuki (Wiley Subscription Services, Inc., A Wiley Company, 2010)

(untitled) (J Med Virol)
Several novel viruses have been recently identified in respiratory samples. However, the epidemiology of these viruses in tropical countries remains unclear. The aim of the present study was to provide an overview of the epidemiology of novel respiratory viruses, including human metapneumovirus, human bocavirus, new subtypes of human coronavirus (NL63 and HKU1), KI virus, WU virus, and Melaka virus in the Philippines, a tropical country. Nasopharyngeal aspirates from 465 patients with influenza‐like illness were collected in 2006 and 2007. Reverse transcription polymerase chain reaction (RT‐PCR) and PCR were performed to detect viruses from culture‐negative specimens. Human metapneumovirus, human bocavirus, human coronavirus HKU1, KI virus, and WU virus were detected for the first time in the Philippines; Melaka virus was not found. J. Med. Virol. 82:1071–1074, 2010. © 2010 Wiley‐Liss, Inc.